Mass Rearing and Life History Studies of Drosophila Under Laboratory Conditions (Biological Sciences - PJSIR, 2022)
Wild Drosophila flies can be collected on fermentingsugary, flavourous fruits or vegetables [1-2]. Marked differencehave been observed with respect to insecticide resistancebetween laboratory reared flies and those collected freshlyfrom the field [3-4]. As the present workers were embarkingupon genotoxicity as well as resistance studies, mass rearingof resistant and susceptible strains of D. melanogaster, obtainedfrom a Swiss laboratory was of utmost importance. Sixstrains of Drosophila melanogaster,